MODEL MATEMATIKA PENYEBARAN PENYAKIT ANTRAKNOSA PADA TANAMAN CABE DENGAN TINDAKAN PREVENTIF DAN KURATIF - Susriyanti, Mella; Ahmad, Defri (UNIVERSITAS NEGERI PADANG, 2024)
A disease that can affect chili plants is anthracnose. This disease can cause crop loss. The level of spread of this disease depends on control efforts, starting from preventive and moving to curative efforts. The purpose of this study was to form a model, analyse it, and interpret the result of a mathematical model analysis of the spread of anthracnose disease in chilies with preventive and curative measures. This type of research is basic research, and the method used is the descriptive method. The mathematical model formed is the SIRPC model. The SIRPC model is the resultant mathematical model. Two balance point the illness free balance point and the endemic balance point are discovered as a result of the study that has been done. the illness free balance point and the endemic balance point obtained are asymptotically stable. The greater the preventive action, the more the protected population increases and the vulnerable population decreases, while when the curative action is greater, the infected and carrier populations decrease.